Active Deep Learner Experience Learning Design on Islamic Education Learning - Muhammad Rafiq Kurniawan; Komariyatul Mahmuda (STAI Serdang Lubuk Pakam, 2023)
SDIT Kuntum Insan Cemerlang Bondowoso and SMPIT Bina Insan Cemerlang Bondowoso have successfully implemented the learning design for the implementation of the Integrated curriculum compiled by JSIT Indonesia, in this regard, it is certainly necessary to conduct research so that the results are expected to be a model for other institutions. This study aims to analyze the learning design based on Active Deep Learner Experience (ADLX) Integrated curriculum for PAI subjects at SDIT Kuntum Insan Cemerlang Bondowoso and SMPIT Bina Insan Cemerlang Bondowoso. The research method used is qualitative, with data collection techniques of observation, interviews and documentation studies. Data analysis by reducing, displaying, verifying and drawing conclusions and data validity using triangulation and member-check. The results of the study explained that the learning design based on ADLX integrated curriculum in PAI subjects was oriented towards the formation of seven characters, namely: straight aqidah, correct worship, mature personality and noble character, being a serious person, discipline, ability to read, memorize, and understand the Qur'an well, having broad insight into religious and academic fields, having life skills.